Journalism The Ethical Dilemma - Norshira Wan Mohd Ghazali, Wan; Wok, Saodah; Mohamed, Shafizan (IntechOpen, 2023)
Journalism - The Ethical Dilemma seeks to advance scholarly knowledge by encouraging discussion between authors covering multiple branches of the social sciences including communication, media, and journalism. The chapters in this book cover all the conceptual, theoretical, and application aspects of journalism, with a case study in each chapter illustrating the issues being addressed. The book emphasizes that despite the advances in digital media platforms, the basics and principles of journalistic practice are still pertinent. In order to stay relevant in the fluidity of digital media, journalists should work on establishing networks with academics from different fields, and with government, health, and political experts. The book is a useful compilation that will benefit researchers, academics, students, media practitioners, and other stakeholders involved.